Low-dose interleukin-2 selectively corrects regulatory T cell defects in patients with systemic lupus erythematosus. Issue 7 (31st August 2015) - von Spee-Mayer, Caroline; Siegert, Elise; Abdirama, Dimas; Rose, Angelika; Klaus, Anika; Alexander, Tobias; Enghard, Philipp; Sawitzki, Birgit; Hiepe, Falk; Radbruch, Andreas; Burmester, Gerd-Rüdiger; Riemekasten, Gabriela; et al.
Abstract : Objectives: Defects in regulatory T cell (Treg) biology have been associated with human systemic autoimmune diseases, such as systemic lupus erythematosus (SLE). However, the origin of such Treg defects and their significance in the pathogenesis and treatment of SLE are still poorly understood. Methods: Peripheral blood mononuclear cells (PBMC) from 61 patients with SLE and 52 healthy donors and in vitro IL-2 stimulated PBMC were characterised by multicolour flow cytometry. Five patients with refractory SLE were treated daily with subcutaneous injections of 1.5 million IU of human IL-2 (aldesleukin) for five consecutive days, and PBMC were analysed by flow cytometry. Results: Patients with SLE develop a progressive homeostatic dysbalance between Treg and conventional CD4+ T cells in correlation with disease activity and in parallel display a substantial reduction of CD25 expression on Treg. These Treg defects resemble hallmarks of IL-2 deficiency and lead to a markedly reduced availability of functionally and metabolically active Treg. In vitro experiments revealed that lack of IL-2 production by CD4+ T cells accounts for the loss of CD25 expression in SLE Treg, which could be selectively reversed by stimulation with low doses of IL-2. Accordingly, treatment of patients with SLE with a low-dose IL-2 regimen selectively corrected Treg defects also in vivo and strongly expanded the Treg population. Conclusions: Treg defects in patients with SLE are associated with IL-2 deficiency, and can be corrected with low doses of IL-2. The restoration of endogenous mechanisms of immune tolerance by low-dose IL-2 therapy, thus, proposes a selective biological treatment strategy, which directly addresses the pathophysiology in SLE.